Enhanced coagulation index: a potent prognostic indicator for clinical outcomes in non-metastatic breast cancer following surgery and adjuvant therapy - Lu, Bolin; Wu, Ji; Yuan, Mu; Zhang, Xuxu; Qiu, Xing; Bai, Jianyin; Yao, Ming; You, Sainan; Wang, Shanshan; Zhen, Linlin (Frontiers in Oncology, 2025)
BackgroundA significant number of studies have demonstrated a correlation between the prognosis of patients with malignant tumors and a single coagulation marker. However, relatively few studies have examined the correlation between complex coagulation markers. The purpose of this study was to investigate the relationship between the level of complex coagulation markers and nonmetastatic breast cancer patients’ clinical outcomes after receiving comprehensive treatment.MethodsThis retrospective cohort study analyzed the information breast cancer patients treated between January 2016 and December 2018 at the affiliated Suqian hospital of Xuzhou Medical University. Subject-working characteristic curves were used to determine the area under the curve. Multivariate Cox regression models were used to adjust for potential confounders and to assess independent associations between biochemical markers and survival outcomes.ResultsOf the 264 patients with a median age of 48 years, 33 (12.5%) patients experienced a survival event. The X-TILE analysis shows that the best cut-off value for APTT/TT is 1.4, and the 5-year Disease-free survival (DFS) for high APTT/TT (≥1.4) is more limited. The receiver operating characteristic curve decided the APTT/TT performance (AUC=0.685, 95%CI 0.602-0.768). Multivariate Cox regression models showed that increased APTT/TT (HR=4.057, p=0.032) and more lymph node metastases (HR=2.324, p<0.001) were independent prognostic factors for DFS.ConclusionsThis study indicated a pivotal role of the APTT/TT ratio in forecasting the prognosis of breast cancer patients following comprehensive treatment. The findings underscore the utility of integrating coagulation markers, alongside traditional clinicopathological indices, to enhance prognostic assessments in clinical practice.